Development of a luminex-based assay for the detection of anti-capripoxvirus and rift valley fever virus antibodies in domestic ruminants - Berguido, Francisco J.; Settypalli, Tirumala Bharani Kumar; Mbuyi, Curé Georges Tshilenge; Bakhom, Mame Thierno; van Vuren, Petrus Jansen; Pawęska, Janusz T.; Cattoli, Giovanni; Grabherr, Reingard; Lamien, Charles Euloge (Virology journal, 2024)
The three members of the genus capripoxvirus (CaPV), lumpy skin disease virus (LSDV), sheeppox virus (SPPV), and goatpox virus (GTPV) have common hosts and areas of overlapping geographical distribution with Rift Valley fever virus (RVFV). Hence, to ensure more cost-effective disease surveillance we developed and evaluated a Luminex assay for the simultaneous detection of antibodies against CaPV and RVFV in domestic ruminants. In cattle, the assay had a sensitivity (Se) of 98.7% and a specificity (Sp) of 98.3% in detecting anti-LSDV antibodies; both diagnostic parameters were 100% for the detection of anti-RVFV antibodies in this species. In sheep and goats, Se and Sp were 100% for the detection of anti-SPPV and anti-GTPV antibodies while they were 100% and 98.9%, respectively for the detection of anti-RVFV antibody. The assay did not cross react with anti-parapoxvirus antibodies of cattle, sheep, and goats. This multiplex serological assay offers a practical tool for accurate detection and monitoring of the immunological status of domestic ruminant populations against veterinary and socio-economically important capripox- and phleboviral infections, thus has the potential to aid in the strategic application of vaccination programmes.